2022
DOI: 10.1002/jor.25251
|View full text |Cite
|
Sign up to set email alerts
|

Nonsurgical treatment reduces tendon inflammation and elevates tendon markers in early healing

Abstract: Operative treatment is assumed to provide superior outcomes to nonoperative (conservative) treatment following Achilles tendon rupture, however, this remains controversial. This study explores the effect of surgical repair on Achilles tendon healing. Rat Achilles tendons (n = 101) were bluntly transected and were randomized into groups receiving repair or non‐repair treatments. By 1 week after injury, repaired tendons had inferior mechanical properties, which continued to 3‐ and 6‐week post‐injury, evidenced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Inflammatory cytokines activate numerous signalling cascades including c-Jun N-terminal kinase (JNK), mitogen-activated protein kinases (MAPKs), nuclear factor kappa B (NF-κB) and signal transducer and activator of transcription (STATs) in musculoskeletal cell types (Tsai et al 2014 ; McClellan et al 2019a , b ; Wang et al 2019 ; Freedman et al 2022 ). Furthermore, several animal models have implicated these inflammatory signalling pathways within tendon extracellular matrix interactions (Gupta et al 2010 ; Schwartz et al 2015 ; Abraham et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory cytokines activate numerous signalling cascades including c-Jun N-terminal kinase (JNK), mitogen-activated protein kinases (MAPKs), nuclear factor kappa B (NF-κB) and signal transducer and activator of transcription (STATs) in musculoskeletal cell types (Tsai et al 2014 ; McClellan et al 2019a , b ; Wang et al 2019 ; Freedman et al 2022 ). Furthermore, several animal models have implicated these inflammatory signalling pathways within tendon extracellular matrix interactions (Gupta et al 2010 ; Schwartz et al 2015 ; Abraham et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst these, TNFα (tumour necrosis factor alpha) and IL-1β (interleukin 1 beta) are evidenced to be the most potent inducers of a catabolic response, with recent evidence suggesting these inflammatory cytokines in combination with IFN-γ (interferon gamma) have detrimental consequences for tendon cell function in vitro [13]. Inflammatory cytokines stimulate the activation of specific signalling pathways inside the cell, including nuclear factor kappa B (NF-κB), mitogen-activated protein kinase (MAPK), c-Jun N-terminal kinase (JNK), and signal transducer and activator of transcription (STATs) [14][15][16]. Our previous work has demonstrated that in adult tenocytes the adverse effects of TNFα and IL-1β are likely caused by their activation of NF-κB [13,17].…”
Section: Introductionmentioning
confidence: 99%
“…GLI2 and GLI3 were also identified as candidate DSLD genes. GLI3 has been linked to mechanotransduction responses during tendon healing ( Freedman et al, 2022 ). In humans, increased expression of MYL1 has been identified in traumatic rotator cuff tears in female patients, whereas MYL2 is highly expressed in degenerative tears in male patients ( Rai et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%